Highly Diastereoselective Hydrosilane‐Assisted Rhodium‐Catalyzed Spiro‐Type Cycloisomerization of Succinimide and Pyrazolone‐Based Functional 1, 6‐Dienes. Issue 13 (18th May 2021) - Li, Hui‐Lin; Huang, Wei‐Sheng; Ling, Fang‐Ying; Li, Li; Yan, Jun‐Hao; Xu, Hao; Xu, Li‐Wen
Abstract: Organosilicon compounds are important reagents and synthetic intermediates that play a key role in the construction of new materials and complex products. Here we show a highly diastereoselective rhodium‐catalyzed cycloisomerization of 1, 6‐dienes, in which the use of (EtO)3 SiH accelerates the intramolecular cyclization reaction to afford a novel spiro‐fused succinimide and pyrazolone derivatives in moderate to excellent yields as a single diastereoisomer. The proposed mechanism involves an active Rh−H species from the hydrosilane that is the H‐donor in this spiro‐type cycloisomerization reaction. Abstract : A highly diastereoselective rhodium‐catalyzed cycloisomerization of 1, 6‐dienes that is promoted by hydrosilane has been established to afford spiro‐fused succinimide and pyrazolone derivatives in moderate to excellent yields as a single diastereoisomer.